Exploring relationships between shock-induced microstructures and H2O and Cl in apatite grains from eucrite meteorites. (1st June 2021) - Barrett, T.J.; Černok, A.; Degli-Alessandrini, G.; Zhao, X.; Anand, M.; Franchi, I.A.; Darling, J.R.
Abstract: The abundance and isotopic composition of volatile elements in meteorites is critical for understanding planetary evolution, given their importance in a variety of geochemical processes. There has been significant interest in the mineral apatite, which occurs as a minor phase in most meteorites and is known to contain appreciable amounts of volatiles (up to wt. % F, Cl, and OH). Impact-driven shock metamorphism, pervasive within many meteorites, can potentially modify the original signatures of volatiles through processes such as devolatilization and diffusion. In this study, we investigate the microstructures of apatite grains from six eucrites across a broad range of shock stages (S1–S5) using electron backscatter diffraction (EBSD) to explore shock-induced crystallographic features in apatite. New Cl and H abundance and isotopic composition data were collected on moderate to highly shocked samples (S3-S5) by Nano Secondary Ion Mass Spectrometry (NanoSIMS). Previously reported volatile data for S1 and S2 eucrites were integrated with EBSD findings in this study. Our findings indicate that apatite microstructures become increasingly more complex at higher shock stages. At low shock stages (S1–S2) samples display brecciation and fracturing of apatite. Samples in S3 and S4 display increasing crystal plastic deformation indicated by increasing spread in pole figures. At the higher shock stages (S4/S5) there is potential recrystallisation demonstrated by an increased density of subgrain boundaries. The Cl content and δ 37 Cl values of highly-shocked apatite grains range from ∼940 to 1410 ppm and −3.38 to +7.70‰, respectively, within the range observed in less-shocked eucrites. In contrast, H2 O abundances are more variable (from 186 to ∼4010 ppm), however, the measured water content still falls within the range previously reported for low-shock eucrites. The measured δD values range from −157 to +163‰, also within the range of values from known low-shock basaltic eucrites. Weighted averages for both isotopic systems (δD −122 ± 20‰, δ 37 Cl + 1.76 ± 0.66‰) are consistent with the range displayed in other inner Solar System bodies. NanoSIMS isotope images of apatite grains display heterogeneity in their Cl abundance at the nanoscale which increases in complexity with shock stage. This increasing complexity, however, does not correlate with deformation microstructures observed in EBSD or with the Cl isotopic composition at either an inter-grain or intra-grain scale. These findings are similar to analyses of variably shocked lunar apatite and, therefore, apatite appears to be a robust recorder of Cl and H (at least at spatial resolution and precision currently achievable by NanoSIMS) on airless bodies, despite intensive shock.